Cold Water in a Warm World: Investigating the Origin of the Nordic Seas' Unique Surface Properties During MIS 11 - Doherty, John M.; Thibodeau, Benoit (Frontiers in Marine Science, 2018)
Surface waters in the Nordic Seas were colder and fresher throughout the marine isotope stage (MIS) 11 interglacial compared to present day. This has been previously attributed to the continuous delivery of freshwater sourced from large ice structures characteristic of the preceding glacial interval, MIS 12. While it is conventionally believed that high-latitude surface freshening can trigger a reduction of the Atlantic Meridional Overturning Circulation (AMOC), multiple lines of evidence suggest a vigorous AMOC despite elevated freshwater forcing in the Nordic Seas. Here, we review and reanalyze evidence for sea surface properties throughout the Nordic Seas and North Atlantic. We find that surface waters in the Nordic Seas experienced an unusually variable inception of interglacial temperature conditions with multiple high-magnitude cold excursions. While cold events in the North Atlantic were frequently associated with in situ meltwater deposition as reconstructed by ice-rafted debris, this proxy was virtually uncorrelated with cold events in the Nordic Seas. Additionally, stable nitrogen analysis revealed variable levels of nutrient utilization in the Nordic Seas’ surface layer throughout MIS 11. This may reflect a dynamic structure of the upper ocean concomitant with an intermittent rate of freshwater delivery. Based on this combination of evidence, we suggest that the colder and fresher surface layer in the Nordic Seas was supplied from higher latitudes, rather than from locally-sourced iceberg meltwater as is characteristic of North Atlantic forcing. Pairing proxy-based evidence with recent numerical simulations further decouples surface freshening in the Nordic Seas and Greenland meltwater input, discrediting Greenland as a source of freshwater to this region during the later phase of MIS 11. Because the origin of freshwater has implications for its rate of delivery, our study might help to explain the active AMOC despite surface freshening during MIS 11 and should be recognized when considering this interglacial as an analogue for near-future climate change scenarios.